...and Knut's mountain bike has been stolen. - Esanu, Octavian; Lesak, Franziska; de Oliveira Macedo, Gissele; Museum Het Domein, Sittard (Sittard : Museum Het Domein, 2000)
Bijl, Guillaume ; Bouvy, Aline ; Cranston, Meg ; Dragnev, Lilia ; Gander, Ryan ; Gillis, John ; Gverovic, Tina ; Kinoshita, Suchan ; Konrad, Aglaia ; Kool, Renée ; Kroboth, Manfred ; et al.
Second part of the two-volume publication 'Unfortunately last Sunday afternoon somebody left the door open and Knut's mountain bike has been stolen.', Museum Het Domein, Sittard, 27.06.2000 - 20.08.2000
kunstcatalogus